Suppression of ongoing experimental allergic encephalomyelitis (EAE) in Lewis rats: synergistic effects of myelin basic protein (MBP) peptide 68–86 and IL-4 - Xu, L-Y (Blackwell Science Inc, 2000)
Mucosal myelin autoantigen administration effectively prevented EAE, but mostly failed to treat ongoing EAE. Patients with multiple sclerosis (MS), for which EAE is considered an animal model, did not benefit from oral treatment with bovine myelin. We anticipated that autoantigen, administered together with a cytokine that counteracts Th1 cell responses, might ameliorate Th1-driven autoimmune disease, and that nasal administration might considerably reduce the amounts of antigen + cytokine needed for treatment purposes. Lewis rats with EAE actively induced with myelin basic protein peptide (MBP 68–86) and Freund's complete adjuvant (FCA), received from day 7 post-immunization, i.e. after T cell priming had occurred, 120 μg MBP 68–86 + 100 ng IL-4 per rat per day for 5 consecutive days. These rats showed later onset, lower clinical scores, less body weight loss and shorter EAE duration compared with rats receiving MBP 68–86 or IL-4 only, or PBS. EAE amelioration was associated with decreased infiltration of ED1(+) macrophages and CD4(+) T cells within the central nervous system, and with decreased interferon-gamma (IFN-γ) and tumour necrosis factor-alpha (TNF-α) and enhanced IL-4, IL-10 and transforming growth factor-beta (TGF-β) responses by lymph node cells. Simultaneous administration of encephalitogenic peptide + IL-4 by the nasal route thus suppressed ongoing EAE and induced IL-4, IL-10 and TGF-β-related regulatory elements.